Escherichia coli Cells Exposed to Lethal Doses of Electron Beam Irradiation Retain Their Ability to Propagate Bacteriophages and Are Metabolically Active - Hieke, Anne-Sophie Charlotte; Pillai, Suresh D. (Frontiers in Microbiology, 2018)
Bacterial cells exposed to lethal doses of ionizing radiation, i.e. electron beam, are unable to replicate yet they remain metabolically active. To investigate this phenomenon further, we electron beam irradiated Escherichia coli cells to a lethal dose and measured their membrane integrity, metabolic activity, ATP levels and overall cellular functionality in terms of ability to propagate bacteriophages. We also visualized the DNA double-strand breaks in the cells. We used non-irradiated (live) and heat-killed cells as positive and negative controls, respectively. Our results show that the membrane integrity of E. coli cells is maintained and that the cells remain metabolically active up to 9 days post-irradiation when stored at 4°C. The ATP levels in lethally irradiated cells are similar to non-irradiated control cells. We also visualized extensive DNA damage within the cells and confirmed their cellular functionality based on their ability to propagate bacteriophages for up to 9 days post-irradiation. Overall, these findings confirm that lethally irradiated E. coli cells which have extensively damaged DNA are unable to replicate. However, they are metabolically active based on multiple indicators. The ability of bacterial cells to be metabolically active and capable of propagating phages in spite of physically damaged DNA is intriguing and deserves further studies.